IMPLEMENTASI PROGRAM TATA LAKSANA BALITA DENGAN MASALAH GIZI DI KECAMATAN KABANJAHE KABUPATEN KARO - Agitha Hutasoit, Cecilia; Subowo, Ari; Santoso, R. Slamet (Journal of Public Policy and Management Review, 2024)
Lack of healthy nutritional status or more commonly called undernutrition is a state of a person in which the amount of vitality (life force) received is less than the vitality used because the amount of vitality entering is less than the recommended needs. This research is motivated by the stunting rate which is still high in Karo Regency in 2021, namely 25.3%. The sub-district that has the highest number of underweight toddlers who receive supplementary food (people) in Karo Regency in 2016-2020 is Kabanjahe Sub-district. The purpose of this study was to determine how the implementation of the Toddler Management Program with Nutrition Problems in Kabanjahe District, Karo Regency. This research uses the theory of Successful Policy Implementation from Van Meter and Van Horn. Data collection techniques using observation, interviews and literature study. Based on the results of the study, it can be concluded that the implementation of the Toddler Management Program with Nutrition Problems in Kabanjahe District is quite good because of the implementation of aspects of policy standards and objectives; resources; characteristics of the implementing organization; attitudes of the implementers; as well as communication between related organizations and implementation activities. Supporting factors contained in the program are the legitimacy of supporting policies, government support, communication technology and good funding streams. The inhibiting factors in the program are community participation, measurement tools that are not in accordance with standards and regional conditions.